Answer:
D) 1/2(2x-6)=-6 = x = -3
Explanation:
A. x = 3
B. x = 7/3
C. x = 4
D. x = -3
Solve for x:
(2 x - 6)/2 = -6
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (2 x - 6)/2 = -6 by 2:
(2 (2 x - 6))/2 = -6×2
Hint: | Cancel common terms in the numerator and denominator of (2 (2 x - 6))/2.
(2 (2 x - 6))/2 = 2/2×(2 x - 6) = 2 x - 6:
2 x - 6 = -6×2
Hint: | Multiply 2 and -6 together.
2 (-6) = -12:
2 x - 6 = -12
Hint: | Isolate terms with x to the left hand side.
Add 6 to both sides:
2 x + (6 - 6) = 6 - 12
Hint: | Look for the difference of two identical terms.
6 - 6 = 0:
2 x = 6 - 12
Hint: | Evaluate 6 - 12.
6 - 12 = -6:
2 x = -6
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 2 x = -6 by 2:
(2 x)/2 = (-6)/2
Hint: | Any nonzero number divided by itself is one.
2/2 = 1:
x = (-6)/2
Hint: | Reduce (-6)/2 to lowest terms. Start by finding the GCD of -6 and 2.
The gcd of -6 and 2 is 2, so (-6)/2 = (2 (-3))/(2×1) = 2/2×-3 = -3:
Answer: x = -3